(untitled) (International Journal of Engineering and Computer Science, 2014)
In this review paper, we provide a comprehensive review of developments in the field of fractal antenna engineering. First we give brief introduction about fractal antennas and then proceed with its design geometries along with its applications in different fields. It will be shown how to quantify the space filling abilities of fractal geometries, and how this correlates with miniaturization of fractal antennas.